2017
DOI: 10.4338/aci-2016-11-ra-0194
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Team Perceptions of a Portal for Parents of Hospitalized Children Before and After Implementation

Abstract: SummaryBackground. Patient electronic health record (EHR) portals can enhance patient and family engagement by providing information and a way to communicate with their healthcare team (HCT). However, portal implementation has been limited to ambulatory settings and met with resistance from HCTs. Objective. We evaluated HCT perceptions before and 6-months after implementation of an inpatient EHR portal application on a tablet computer given to parents of hospitalized children. Methods. This repeated cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 33 publications
2
49
3
5
Order By: Relevance
“…We found that providers (physicians and nurses) valued the usefulness of EPP (82%). Our providers were overly optimistic about the perceived usefulness of EPP as compared to a study by Kelly et al [71], who found that 53% of health care providers valued EPP as a tool to improve patient quality of care. It is possible that this is partially due to the Lebanese culture, which is often rather quick to adopt a positive attitude toward innovation in general [72] and is a novelty-seeking culture, especially among individuals with higher educational attainment [73].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We found that providers (physicians and nurses) valued the usefulness of EPP (82%). Our providers were overly optimistic about the perceived usefulness of EPP as compared to a study by Kelly et al [71], who found that 53% of health care providers valued EPP as a tool to improve patient quality of care. It is possible that this is partially due to the Lebanese culture, which is often rather quick to adopt a positive attitude toward innovation in general [72] and is a novelty-seeking culture, especially among individuals with higher educational attainment [73].…”
Section: Discussioncontrasting
confidence: 77%
“…Given that different cultures react differently to the use of EPP and given the rise in its use, it was important to examine the intention to use to provide decision-makers with an empirical tool that would potentially enhance the actual use. Globally, portal developers, researchers, and practitioners would also benefit from the findings when targeting patients from different cultural backgrounds [71].…”
Section: Discussionmentioning
confidence: 99%
“…Most thought the portal would improve care quality, but also increase their workload. Kelly et al 22 examined the effects of inpatient portal use on clinicians working on a pediatric medical/surgical unit before and 6 months after implementation and found similar results. Only one published study has evaluated health care team perceptions of an inpatient portal after system-wide implementation across multiple hospitals.…”
Section: Background and Significancementioning
confidence: 88%
“…Given that different cultures react differently to the use of EPP and given the rise in its use, it was important to examine the intention to use to provide decisionmakers with an empirical tool that would potentially enhance the actual use. Globally, portal developers, researchers, and practitioners would also benefit from the findings when targeting patients from different cultural backgrounds (71).…”
Section: Discussionmentioning
confidence: 99%